Physicochemical evaluation, structural characterization, in vitro and in vivo bioactivities of water-soluble polysaccharides from Luobuma (Apocynum L.) tea - Abubakar, Aminu Shehu; Ahmad, Bilal; Ahmad, Nabi; Liu, Liangliang; Liu, Bin; Qu, Yatong; Chen, Jikang; Chen, Ping; Zhao, Haohan; Chen, Jia; Chen, Kunmei; Gao, Gang; et al. (Food chemistry, 2024)
Luobuma tea is made from the leaves of Apocynum hendersonii (Bt) and A. venetum (Ht) and has been used for a very long time in China and Japan as herbal tea. This study isolated water-soluble polysaccharides from the two species` teas. Physicochemical properties, structural properties, in vitro and in vivo antioxidant and immunomodulatory activities were determined for the first time. The results showed that the Bt and Ht polysaccharides with molecular weights of 31.21 and 49.11 kDa, respectively, composed of arabinose, galactose, rhamnose, glucose, xylose, fucose, and mannose. A dose-dependent nitric oxide production and interleukin-6 inhibitory effects were obtained. Also, they suppressed the expression of cyclooxygenase-2, tumor necrosis factor-α and interleukin-6 mRNA in LPS-induced RAW 264.7 macrophages. Likewise, Bt and Ht have significantly reduced edema in the paws of mice after carrageenan injection. These results suggested that the Luobuma teas polysaccharides can be explored as potential antioxidants and anti-inflammatory agents. •A soluble polysaccharides (Bt and Ht) were extracted from Luobuma (Apocynum L.) tea.•Physico-chemical and structural properties of the Bt and Ht were investigated.•Bt and Ht have inhibited the production of interleukin-6 inflammatory mediator in macrophages.•Bt and Ht have significantly reduced edema in the paws of mice after carrageenan injection.